Photothermal Therapy: Metabolizable Ultrathin Bi2Se3 Nanosheets in Imaging‐Guided Photothermal Therapy (Small 30/2016). Issue 30 (5th August 2016) - Xie, Hanhan; Li, Zhibin; Sun, Zhengbo; Shao, Jundong; Yu, Xue‐Feng; Guo, Zhinan; Wang, Jiahong; Xiao, Quanlan; Wang, Huaiyu; Wang, Qu‐Quan; Zhang, Han; Chu, Paul K.
Abstract : Ultrathin Bi2 Se3 nanosheets are prepared by a solution method. As described on page 4136 by X.‐F. Yu, Q.‐Q. Wang, P. K. Chu, and co‐workers, such ultrathin Bi2 Se3 nanosheets exhibit strong near infrared (NIR) light absorption, excellent photothermal and photoacoustic performance, enabling efficient imaging‐guided photothermal therapy. Furthermore, these Bi2 Se3 nanosheets are well metabolized. These attractive properties render the Bi2 Se3 nanosheets promising as a NIR‐triggered theranostic agents in cancer therapies.